The Current Transformer Parameters Investigation and Simulations - Rafajdus, P.; Braciník, P.; Hrabovcová, V. (Elektronika ir Elektrotechnika, 2010)
This paper deals with current transformer (CT) analysis and simulations of transients. The parameters of CT equivalent circuit for protective winding are measured and used in its mathematical model. The B-H curve is included into mathematical model of transformer and it is expressed by function of magnetizing inductance versus magnetizing current. The simulated current results of sudden short circuit in the network are compared with measured ones. Ill. 12, bibl. 6 (in English; abstracts in English, Russian and Lithuanian).